Geophysical Case Study of the Iso and New Insco Deposits, Québec, Canada, Part II: Modeling and Interpretation - L. Z. Cheng; R. S. Smith; M. Allard; P. Keating; M. Chouteau; J. Lemieux; M. A. Vallée; D. Bois; D. K. Fountain (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
"Abstract - MEGATEMII airborne electromagnetic data collected over the Iso and New Insco massive sulfide deposits have been modeled using three modeling packages. The EMQ package is a quick inversion tool which indicates that the Iso body is a dipping, plate-like body. The New Insco body is inferred to have a geometry somewhere between a dipping plate and a sphere. The Maxwell package was used to refine the properties of the plate-like body at Iso. The EMIGMA package was able to identify which parts of the New Insco orebody were more conductive. It was observed that the most conductive parts correspond to copper-rich zones and the next most conductive to pyrite-rich zones. The EMIGMA package was also used to show that a thick-prism model might be more appropriate for the New Insco orebody. Gravity modeling constrained by the known geology was successful in identifying the denser sulfide zones. The densest zones appear to be pyrite rich. Magnetic modeling identified diabase dikes. Over New Insco, a small magnetic anomaly was attributed to pyrrhotite-rich sulfides. There was only a weak magnetic anomaly over the Iso body, consistent with the nonmagnetic sulfides logged in the holes drilled at that location. Sommaire - Les données MEGATEMII recueillies au-dessus des dépôts d’Iso et de New Insco ont été interprétées en utilisant trois outils de modélisation différents. L’outil EMQ a été utilisé comme un outil d’inversion rapide suggérant que le dépôt Iso peut être considéré comme une plaque inclinée, et que le dépôt de New Insco se situe quelque part entre une plaque et une sphère. L’outil Maxwell a été utilisé pour raffiner les propriétés du dépôt Iso. L’outil EMIGMA nous a permis d’identifier les différences de conductivité à l’intérieur du dépôt Iso. Il a été observé que la partie la plus conductrice correspond à la zone riche en cuivre, suivie par la zone riche en pyrite. L’outil EMIGMA a aussi permis de montrer qu’un modèle de prisme épais pourrait être plus approprié pour décrire le dépôt New Insco. La modélisation des données gravimétriques, contrainte par la géologie connue, définit bien la zone de sulfures massifs. La zone de pyrite semble être la plus dense. La modélisation des données magnétiques identifie bien les dykes de diabase. Au-dessus du dépôt New Insco, on observe une faible anomalie magnétique correspondant aux sulfures non magnétiques observés dans les carottes de forages à cet endroit."